Exploring Gen Z Consumers’ Impulse Buying Behaviour on E-commerce: An SDL Perspective - Kholida, Arifa; Puspita Rini, Gilang (Economics and Business Solutions Journal, 2025)
This study discusses the relationship between E-WOM and impulsive buying to help e-commerce implement the right marketing strategy to increase sales. This study aims to test the role of E-WOM in increasing impulsive buying by developing a theoretical framework. The respondents used in this study were 125, and the incoming data was processed using SPSS 26. The results of this study indicate that E-WOM has a positive and significant effect on impulsive buying. This study also studied other variables, namely shopping lifestyle, sales promotion, and economic literacy, which showed a positive and significant effect on impulsive buying. This study will contribute to future research on impulsive buying and other research related to e-commerce users, especially in Generation Z